Pandangan Majelis Permusyawaratan Ulama Aceh Terhadap Sertifikasi Halal Produk Home Industry di Kota Banda Aceh - Faiyadh Musaddaq (Journal of Islamic Business Law, 2017)
This study aims to examine the role of Majelis Permusyawaratan ulama Aceh on halal certification of home industry products in Banda Aceh City. The availability of various foods makes it easy for people to get it. On the other hand halal food products can be questioned. Guarantee halal of a food product can be realized among them in the form of halal certificate that accompanies a food product. The Majelis Permusyawaratan Ulama (MPU) through the LPPOM of the Ulema Council of Ulama which is authorized to grant halal certification. The type of this research is field research / empirical with qualitative descriptive approach. Primary data comes from interviews and secondary data derived from related literature. The results show that LPPOM Aceh has socialized the importance of halal food products, but not maximally to all areas, such as Banda Aceh and Aceh Besar located in the city center but not yet fully resolved. Viewpoints and attitudes of market participants in Aceh, be it producers and consumers who tend apatis and a priori with halal labelisasi on any product they consume to be an obstacle.Keyword: Halal certification, home industry product